A new generalized contraction and its application in dynamic programming. Issue 1 (1st January 2018) - Ramezani, M.; Ramezani, H.
Abstract: By using the idea of Pata [ V. Pata, A fixed point theorem in metric spaces. J. Fixed Point Theory Appl. 10 (2011) 299–305 .] we establish a new common fixed point theorem and as an application, we prove the existence and uniqueness of common solutions for a class of system of functional equations arising in dynamic programming.